2015
DOI: 10.1186/s13031-015-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

Conflict, displacement and sexual and reproductive health services in Mali: analysis of 2013 health resources availability mapping system (HeRAMS) survey

Abstract: ObjectiveLittle is known specifically about the effects of conflict and displacement on provision of sexual and reproductive health (SRH) services. We aimed to understand the association between levels of conflict and displacement and the availability of SRH services in post-conflict Mali.MethodsA national assessment was conducted between April and May 2013 employing Health Systems Availability Mapping System (HeRAMS). Data from 1581 primary care facilities were analysed, focusing on SRH services. Descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
0
20
0
2
Order By: Relevance
“…8 MPA, with support from the Malian army, fought against the Popular Liberation Front of Azawad and ARL. 9 Tuncalp et al (2015) analyzed data on health-care facilities collected during the 2012 northern Mali conflict and found that facilities in conflict areas lacked several services such as prenatal care, skilled care during childbirth, and postnatal care because of the medical supply chain, and even qualified health-care workers. 10 Table A1 in the Appendix provides detailed information on these conflicts.…”
Section: Endnotesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 MPA, with support from the Malian army, fought against the Popular Liberation Front of Azawad and ARL. 9 Tuncalp et al (2015) analyzed data on health-care facilities collected during the 2012 northern Mali conflict and found that facilities in conflict areas lacked several services such as prenatal care, skilled care during childbirth, and postnatal care because of the medical supply chain, and even qualified health-care workers. 10 Table A1 in the Appendix provides detailed information on these conflicts.…”
Section: Endnotesmentioning
confidence: 99%
“…It was observed in the Malian conflict that in areas with fierce battles, regular markets were closed and access to health facilities was disrupted (Tuncalp et al, 2015), and the security was compromised such as robbery and private punishment (Poulton & ag Youssouf, 1998). There must have been other ways that conflict affects civilians (Kadir, Shenoda, & Goldhagen, 2019).…”
mentioning
confidence: 99%
“…In comparison, Senegal is considered to be one of the more politically stable countries in West Africa [7]. According to Tunçalp et al (2015), significant strains were placed on the few reproductive services available in the south of Mali as more internally displaced women relocated there [8]. However, the health systems in both countries have been severely compromised by a long-term lack of investment [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned challenges of delivering patient-centred care in sub-Saharan Africa, providers in Mali face unique challenges of maintaining quality services in a highly decentralised, primary healthcare system 28 and ensuring access to care in hard-to-reach rural and conflict-ridden areas. 29 Our objectives were to assess patient-centred attitudes among medical students, determine if patient-centred attitudes vary according to academic year and demographic factors and test the construct validity and internal consistency of the PPOS in this setting.…”
Section: Introductionmentioning
confidence: 99%